Degradation of IL-4Ralpha by Immunoproteasome: implication in airway type 2 inflammation and hyperresponsiveness - Schaunaman, Niccolette; Cervantes, Diana; Ferrington, Deborah A.; Chu, Hong Wei (Frontiers in Immunology, 2025)
IntroductionImmunoproteasome (IP) is induced by pro-inflammatory stimuli such as interferon gamma to regulate inflammation and immunity. Asthma patients with airway type 2 high inflammation (e.g., IL-13) demonstrate more eosinophils and airway hyperresponsiveness (AHR) with less interferon gamma. The role of IP in regulating airway eosinophilic inflammation and AHR has not been investigated.MethodsThis study was aimed to determine how IP regulates type 2 inflammation and AHR using LMP7 (a subunit of IP) deficient mouse lungs, precision-cut lung slices (PCLS), and cultured human airway epithelial cells treated with IL-13 in the absence or presence of an IP inhibitor ONX-0914 or exogenous IP.ResultsLMP7 KO mouse lungs had significantly more IL-4Rα protein expression than the wildtype (WT) mice. Following IL-13 treatment in PCLS, LMP7 KO mice had significantly more airway contraction than WT mice, which was coupled with increased eotaxin-2 levels. IP inhibition by ONX-0914 in IL-13 treated human airway epithelial cells resulted in significantly more IL-4Rα protein expression and eotaxin-3 release. IP inhibition in human PCLS significantly increased AHR.ConclusionCollectively, these data demonstrated that IP promotes degradation of IL-4Rα, while inhibits type 2 inflammation and AHR. Enhancement of IP expression or activity may serve as an alternative approach to reduce the severity of type 2 inflammation and AHR.